Individual earnings and household incomes: mutually reinforcing inequalities? - Wiemer Salverda (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
Inequality's rise and impacts deservedly receive much attention in scientific and public debates, with most of the attention being paid to the very top of the income or wealth distribution. This contribution complements this with a study of the broader top – the top 10 per cent – where labour-market outcomes play a predominant role. However, the analysis still needs to come to terms with the death of the single-breadwinner model and its replacement with two or more earners in the household. At the same time this brings in the (household distribution of) hours of work as an important new dimension of inequality, in addition to the traditional wage levels. It will be shown, using data for 26 EU countries, that these changes complicate the linkages of wage inequality and income inequality and add to the importance of employee earnings for income inequality. For this analysis, aggregate inequality measures will be put aside in favour of a more detailed consideration across the distributions of earnings and incomes. Some implications for analysis and policy are discussed in the conclusion.
Keywords: J21; J22; J31; H31; 330; income inequality; wage inequality; top incomes; breadwinner model; household labour supply